Emergence of a New Epidemic Neisseria meningitidis Serogroup A Clone in the African Meningitis Belt: High-Resolution Picture of Genomic Changes That Mediate Immune Evasion - Araceli Lamelas (American Society for Microbiology, 2014)
ABSTRACT In the African “meningitis belt,” outbreaks of meningococcal meningitis occur in cycles, representing a model for the role of host-pathogen interactions in epidemic processes. The periodicity of the epidemics is not well understood, nor is it currently possible to predict them. In our longitudinal colonization and disease surveys, we have observed waves of clonal replacement with the same serogroup, suggesting that immunity to noncapsular antigens plays a significant role in natural herd immunity. Here, through comparative genomic analysis of 100 meningococcal isolates, we provide a high-resolution view of the evolutionary changes that occurred during clonal replacement of a hypervirulent meningococcal clone (ST-7) by a descendant clone (ST-2859). We show that the majority of genetic changes are due to homologous recombination of laterally acquired DNA, with more than 20% of these events involving acquisition of DNA from other species. Signals of adaptation to evade herd immunity were indicated by genomic hot spots of recombination. Most striking is the high frequency of changes involving the pgl locus, which determines the glycosylation patterns of major protein antigens. High-frequency changes were also observed for genes involved in the regulation of pilus expression and the synthesis of Maf3 adhesins, highlighting the importance of these surface features in host-pathogen interaction and immune evasion. IMPORTANCE While established meningococcal capsule polysaccharide vaccines are protective through the induction of anticapsular antibodies, findings of our longitudinal studies in the African meningitis belt have indicated that immunity to noncapsular antigens plays a significant role in natural herd immunity. Our results show that meningococci evade herd immunity through the rapid homologous replacement of just a few key genomic loci that affect noncapsular cell surface components. Identification of recombination hot spots thus represents an eminent approach to gain insight into targets of protective natural immune responses. Moreover, our results highlight the role of the dynamics of the protein glycosylation repertoire in immune evasion by Neisseria meningitidis. These results have major implications for the design of next-generation protein-based subunit vaccines.